Information Poverty: Kemiskinan Informasi dan Peranan Perpustakaan dalam Pengentasannya - Himayah Himayah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2013)
Information and communication technology (ICT) plays an important role in classifying the world in information richand information poor. Poverty is not only limited information by